Restoration through redemption : John Calvin revisited - Belt, H. van den, 1971- (Studies in Reformed Theology, 2013)
Restoration through Redemption offers examples of three ways in which John Calvin's theology can be revisited: by analysis, assessment, and reception. This volume contains analyses of Calvin's position on the trinity and on politics, as well as assessments of his theology for evolutionary biology and comparative ecclesiology. It also discusses the reception of his heritage, for instance, in North America and South Africa. The central theme in this volume is Calvin's approach to the renewal of creation that hinges on Christ the Redeemer. One of the golden threads is Calvin's emphasis upon the meditatio on the future life, the turning of the believer towards the eschatological perspective. Contributors include: J. Todd Billings, Johan Buitendag, Jaeseung Cha, Ernst M. Conradie, Roger Haight, I. John Hesselink, Rinse Reeling Brouwer, Philippe Theron, Henk van den Belt, Gijsbert van den Brink, Cornelis van der Kooi, J.H. (Amie) van Wyk, J.M. (Koos) Vorster, Nico Vorster, Robert Vosloo, and Paul Wells.